2015
DOI: 10.1142/s021909151550006x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Rebalanced and Buy and Hold Portfolios: Does Monetary Policy Matter?

Abstract: We examine buy and hold and a number of rebalancing strategies on a portfolio of indices that are tracked by ETFs. The indices include Barkley's treasuries and MSCI indices on emerging markets, Pacific and European markets, value funds, and growth funds. Portfolios are rebalanced using threshold schemes and compared with portfolios rebalanced using weights from different points on the Markowitz efficient frontier. We also examine portfolios that are rebalanced across monetary policy regimes. We find that portf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Stock markets affect the economy via two channels. The first channel is through the wealth effects and second channel is that they are seen as avenues through which consumers and corporate organizations express their confidence in the economy and invariably react to monetary policy decisions as reported in Hilliard and Hilliard (2015). This is further buttressed by the argument of PWC (2013) that both the US and the UK stock markets recorded resilient rises during the fourth quarter of 2013 through to the middle of first quarter of 2013 even in the face of negative growths reported by the countries for the period.…”
Section: Figurementioning
confidence: 99%
“…Stock markets affect the economy via two channels. The first channel is through the wealth effects and second channel is that they are seen as avenues through which consumers and corporate organizations express their confidence in the economy and invariably react to monetary policy decisions as reported in Hilliard and Hilliard (2015). This is further buttressed by the argument of PWC (2013) that both the US and the UK stock markets recorded resilient rises during the fourth quarter of 2013 through to the middle of first quarter of 2013 even in the face of negative growths reported by the countries for the period.…”
Section: Figurementioning
confidence: 99%
“…The researchers concluded that if the investors find it difficult to rebalance the portfolio than there is a small difference between the risk adjusted return of buy and hold and rebalancing strategies. Hilliard and Hilliard (2015) examined the buy and hold strategy using the portfolio of indices that were tracked through ETFs. The data collected was based on the monthly data ranged from 6-30-1992 until 10-31-2011.…”
Section: Literature Reviewmentioning
confidence: 99%